Two new species of flattie spiders (Araneae: Selenopidae) and descriptions of undescribed males from the Caribbean - Crews, Sarah C. (Zootaxa, 2018)
Two new species of Selenops, S. anacaona sp. nov. (♀) and S. caonabo sp. nov. (♀), are described from the Dominican Republic on the Caribbean island of Hispaniola. These two new species increase the number of endemic Selenops on Hispaniola to 13, surpassing Cuba, which currently has 11 endemic species. Additionally, the male of S. pensilis Muma, 1953 from Hispaniola is described, as well as the male of S. petrunkevitchi Alayón, 2003 from Jamaica. Full distribution records are given for the new species and the newly described males, and new records are provided for the following species: S. aequalis Franganillo, 1935, S. bocacandensis Crews, 2011, S. candidus Muma, 1953, S. micropalpus Muma, 1953, S. morro Crews, 2011, S. simius Muma, 1953, S. souliga Crews, 2011, and S. submaculosus Bryant, 1940.